Local policies and interventions to reduce a city’s carbon footprint using plant-based diets: bristol as a case study - Roberto Rivera Fernandez; James Longhurst; Jo Barnes (Environmental Research: Food Systems)
Net zero strategies are needed to mitigate the effects of the climate emergency. Food systems are responsible for one third of global GhG emissions. This study explores policies and interventions that can be applied at a local level to decarbonise the food system in the UK, using Bristol as a case study. Online elite interviews were conducted with 12 key stakeholders (policymakers, communities, and businesses). Through their lenses, potential interventions were identified that could promote behaviour change and enable a shift towards low-carbon plant-based diets in Bristol. Interventions are presented in an impact-effort matrix and include action on public procurement, community market gardens and food choice architecture. Although stakeholders think these interventions could be impactful, they also identified significant barriers, such as the need for specific subsidies/funding, resistance to change, and misinformation that will need to be overcome for the interventions to be implemented. The discussion provides examples of how each stakeholder group in the study could get involved to address the interventions proposed by the interviewees, concluding that further research is needed to explore the perspective of other key stakeholders (e.g. public) and different layers of governance (e.g. regional) to reach more holistic and comprehensive outcomes.